Evaluasi Teknis Pengolahan Batu Granit Untuk Pencapaian Target Produksi 40.000 Ton/Bulan Pada PT Bumiwarna Agung Perkasa Di Desa Air Mesu Timur Bangka Tengah - Reza Reza; E.P.S.B Taman Tono; Delita Ega Andini (Jurusan Teknik Pertambangan Universitas Bangka Belitung, 2019)
PT Bumiwarna Agung Perkasa, abbreviated as PT BWAP has a crushing plant which is divided into two units, namely primary crusher and the secondary crusher unit. Granite stone crushing plant of PT BWAP has production target 40.000 tons/month, but the production target has not been achieved, which 15.185,21 tons on June and 23.406,94 tons on July 2018, because there are production barriers which cause the available work of these two units to reduce and improve production targets, therefore to achieve production targets, evaluation of the demolition plant is needed. The method used in this study is the tool availability method. The data needed is the speed of feed raw material, tool working time, tool standby time and the weight of product samples taken on the conveyor belt. The main calculation of the primary primary crusher unit is very low at 32,67 % with a total production of only 26.940,20 tons/month and the secondary crushing unit is also very low at 42,45 % with a total production of 20.424,92 tons/month. After repairs, the working efficiency of the primary crusher unit increased to 75,69 % and the work efficiency of the secondary crusher increased to 78,15 % and to increase feeding to the secondary crusher unit, activating the two vibro feeders, so that the feed increased from 190,34 tons/hour to 260,06 tons/hour and the final production of crushing plant increased to 53.352 tons/month.